"Stay away from the Park": A Case for Police-Issued Personal Safety Advice for Women - Minehan, Matthew John (Ethical theory and moral practice, 2024)
Are police officers morally justified in issuing unsolicited personal safety advice to women? Such advice often attracts accusations of "victim blaming", although prevention advice remains a common tool used by police to address many crime and safety risks. While some examples of police advice are clearly outrageous, this article considers whether there is a place for "sound" advice, i.e., advice that is proportionate, easy to follow, empirically justified, and objectively likely to reduce harm. To explore this, the article proposes a thought experiment that compares safety advice dealing with threats to women from human sources with safety advice issued in response to natural phenomena, such as flooding. It argues that, despite apparent differences, safety advice addressing risks from humans and natural phenomena are relevantly similar. Consequently, if advice dealing with natural phenomena is morally justified then advice to women about human threats is also morally justifiable. Nevertheless, the article also considers whether the purported prevalence of sexism in policing may make safety advice for women morally problematic. While levels of sexism in policing may vary across time and location, it is argued that safety advice would be morally justified even if sexism was widespread among police officers. Finally, the article considers whether crime prevention advice may backfire by effectively curtailing women’s freedoms. Rather than curtailing freedom, however, it is argued that sound advice may actually enable women to flourish by helping them overcome fear of crime and achieve non-instrumental goals that they have set for themselves.